Does postoperative infection after soft tissue sarcoma resection affect oncologic outcomes?. Issue 5 (28th November 2013) - Behnke, Nicole K.; Alamanda, Vignesh K.; Song, Yanna; Archer, Kristin R.; Halpern, Jennifer L.; Schwartz, Herbert S.; Holt, Ginger E.
Abstract Background and Objectives Prior studies have demonstrated postoperative infection may confer a survival benefit after osteosarcoma resection. Our aim was to determine whether infection after soft tissue sarcoma resection has similar effects on metastasis, recurrence and survival. Methods A retrospective review was conducted; 396 patients treated surgically for a soft tissue sarcoma between 2000 and 2008 were identified. Relevant oncologic data were collected. Fifty‐six patients with a postoperative infection were compared with 340 patients without infection. Hazard ratios and overall cumulative risk were evaluated. Results There was no difference in survival, local recurrence or metastasis between patients with or without a postoperative infection. Patients were evenly matched for age at diagnosis, gender, smoking status, and diabetes status. Tumor characteristics did not differ between groups in tumor size, location, depth, grade, margin status, stage, and histologic subtype. There was no difference in utilization of chemotherapy or radiation therapy between groups. From our competing risk model, only positive margin status significantly impacted the risk of local recurrence. An increase in tumor size corresponded to an increased risk of metastasis and death. Conclusions Postoperative infection neither conferred a protective effect, nor increased the risk of adverse oncologic outcomes after soft tissue sarcoma resection. J. Surg. Oncol. 2014 109:415–420. © 2013 Wiley Periodicals, Inc.